Assessing the effects of salinity and inundation on halophytes litter breakdown in Yellow River Delta wetland. (August 2020) - Zhai, Jiexiu; Yan, Guoxin; Cong, Ling; Wu, Yanan; Dai, Liyi; Zhang, Zhenming; Zhang, Mingxiang
Highlights: Decomposition rate and effects were measured in field and laboratory experiments. Measured soil properties and PLFAs for decomposition at different salinities and inundation environments. Decomposition rate was correlated with water quality and fungal microbe content. Leaf litter may control carbon cycling and energy flow in estuary ecosystems. Artificially elevating wetland nutrient content may mitigate negative human impact. Abstract: Decomposition of halophyte litter may considerably influence carbon cycling and energy flow in estuarine ecosystems. We examined water quality parameters, soil properties, and soil phospholipid fatty acid (PLFA) contents from the Yellow River Estuary, China, to investigate Phragmites australis and Suaeda glauca litter decomposition dynamics. Surface soils (0–10 cm) under three different salinity conditions were collected from six plots. Results showed that the litter decomposition rate of S. glauca (k = 0.0063) was significantly (p = 0.032) higher than that of P. australis (k = 0.0024). Litter decomposition rate had a significant (p < 0.01) relationship with water compositional parameters (water dissolved oxygen, temperature, chemical oxygen demand, and NH3 -N). According to the results of our surface soil analysis, in plots with 1% salinity, values for total soil PLFAs, bacterial PLFAs, Gram-negative PLFAs, and fungal PLFAs were all higher after 270 days than after 120 days. Fungi were the principal microbial group responsible for leaf litter decay. Changes in the nutrient utilization of litter may result in changes in the allocation of resources for growth and reproduction, which suggests that artificial elevation of wetland nutrient content may mitigate the negative human impacts associated with climate change. This study demonstrated the effects of biotic (litter types, activities of microbial organisms) and abiotic (salinity, inundation) variables on halophyte litter decomposition in Yellow River Delta wetlands.